Analysis Of Career Planning Management At Pt. Bank Btpn Syariah Tbk. - Ferry Setyadi Atmadja; Susan Febriantina; Chaerunisha Aila Widarum; Keisya Puteri Debi; Kayla Rahma Anjani; Nur Azizah; Adin Nur Rahman (Journal of Innovative and Creativity, 2025)
Objective: PT Bank BTPN Syariah Tbk. manages career planning and development by taking action by providing a Hari Raya Allowance twice the salary, the opportunity to travel abroad, an undergraduate scholarship program, housing facilities, and work vehicles. This research aims to understand the stages of Human Resources in designing PT Bank BTPN Syariah Tbk employees' careers. Methodology: This research uses a descriptive qualitative method with previous research related to this research as a reference. The sources of information studied came from national journals and interviews with the Human Capital Business Partner of PT Bank BTPN Syariah, Tbk. Results: A well-executed performance review process will provide valuable data for future workforce planning and development strategies. Information gathered from reviews can be instrumental in identifying skills gaps, understanding training needs, and preparing employees for industry advancements. This data-driven approach ensures that employees are ready for future changes in industry or technology but also allows the organization to remain competitive by strategically investing in its workforce. Limitations: The limitation of this study lies in the fact that it was only conducted on one employee in one company at BTPN Syariah. This can limit the generalization of research results to a broader population, as the dynamics of work ethic and career paths can differ across different organizations or sectors. In addition, an employee's career path is often influenced by other factors, such as education level, experience, and interpersonal relationships, which, if not considered in the analysis, can lead to an inaccurate correlation between each employee's work ethic and career path. Contribution: This research is helpful for further research on human resource planning and development in Islamic banking. Novelty: An employee career planning program with a one-to-one evaluation method with superiors will produce the quality of employee performance by the company's management standards. Effective career planning, which includes career education, career counseling, and career evaluation, is essential for achieving organizational goals and improving organizational structure stability.